Laterality of proprioception in the orofacial muscles and temporomandibular joint. (2nd December 2016) - Frayne, Ellie; Coulson, Susan; Adams, Roger; Croxson, Glen; Waddington, Gordon
Highlights: Closure movement proprioception is better at lips than jaw. Lip and jaw proprioceptive acuity are correlated on the right side but not on the left. Right side lips had higher discrimination acuity than left only for small objects. Findings consistent with use-based proprioception enhancement and matching for coordinated function. Abstract: Laterality of function in the orofacial musculature suggests there may be side-to-side asymmetry of proprioceptive acuity in lip movement compared to the temporomandibular joint (TMJ). In the present work, 14 young adults were tested for acuity of lip and TMJ closure movements onto plugs varying from 5 to 8 mm without visual feedback. Testing was conducted on both left and right sides, using the same psychophysical task and stimuli. Results showed superior proprioceptive acuity at the lips, with no significant side effect. However, there was side-to-side asymmetry in the correlations between proprioceptive performance for the two anatomical structures, with performance on the right side strongly correlated but not on the left. This is consistent with the need for coordination between structures during chewing. When acuity at different points in the stimulus range was examined, the right side lips were better with small stimuli. Overall, results support enhanced use-specific proprioception.